18F-FDG positron emission tomography computed tomography and the "underground map" appearance in imaging Horton's arteritis - Abdul Jalil, Nordin; Abdul Rahim, Noraini; Md Shalleh, Nursuzaili; Rossetti, Claudio (Singapore Medical Association, 2008)
A majority of the clinical use of positron emission tomography (PET)-computed tomography (CT) is related to cancer management. Its application in evaluating inflammatory diseases and pyrexia of unknown origin is becoming popular. We reviewed the fluorine-18-fluorodeoxyglucose PET-CT findings of an 80-year-old woman with nonspecific clinical presentation consisting of generalised malaise, moderately high fever and weight loss. Prior CT and magnetic resonance imaging were not helpful in providing a clinical diagnosis. The diagnosis was Horton's arteritis, and the patient responded well to high-dose steroids.